HUBUNGAN AKTIVITAS BELAJAR DAN MOTIVASI DENGAN HASIL BELAJAR TAHFIZ AL-QUR’AN (STUDI PADA MTS DARUL QUR’AN DELI SERDANG) - Moncot Moncot (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to examine the relationship of learning and motivationactivities with student learning outcomes in the field of study Tahfiz Al-Qur'an in MTs. Darul Qur'an Deli Serdang Regency. This research isproposed by testing three hypotheses, namely First: There is a relationship of learning activities with student learning outcomes in the field of study Tahfiz Al-Qur'an in MTs. Darul Qur'an Deli Serdang Regency. Second, there is a relationship of learning motivation with student learningoutcomes of tahfiz Qur'an in MTs. Darul Qur'an Deli Serdang Regency.Third, there is a relationship of learning activities and motivation withstudent learning outcomes in the field of study Tahfiz Al-Qur'an in MTs.Darul Qur'an Deli Serdang Regency.The population of this study werestudents of MTs. Darul Qur'an academic year 2017/2018 amounted to 176people. The technique used to determine the sample size is Arikuntoformula. By using the formula, the sample is 30 students. Data collectionfor learning activity variables and learning motivation in this study usinga questionnaire with Likert model scale. While for the variable of studentlearning result of data collecting obtained from document of raport value.Based on the test results on the reliability of these two questionnairevariables obtained the coefficient of reliability as follows: learning activityvariables 0,939 and, Learning motivation variables 0,986. The result of first hypothesis analysis by using correlation technique and regression either simple or multiple obtained ry.1 = 0,392, while R2 y.1 = 0,154. This means that the relationship shown by the variable learning activities with student learning outcomes is strong and very significant. Regression analysis obtained by the equation of simple regression line is Ý = 37,77 + 0.46X1.Results of the second hypothesis analysis show that ry.2 = 0,405., While R2 y.2 = 0,164. This means that the relationship shown by the variablemotivation to learn with student learning outcomes is strong and verysignificant. Regression analysis obtained by the equation of simpleregression line is Ý = 41,29 + 0,18X2. While the third hypothesis shows that ry1.2.3 = 0,501., While Ry1.2.3 = 0,252. Through regression analysis we get the equation of multiple regression line is Ý = 50,42 + 0,36X1 + 0,15X2.